Family involvement in early education and child care - Sutterby, John A., 1966- (Advances in early education and day care, 2017)
This volume encourages reflection on previous volumes. Family involvement has been an issue in early education going back to Pestalozzi almost two centuries ago. This book looks at what advances in the area of family involvement in early education have been made since the publication of the previous volume.